Body Composition Changes in Adult Females after Lifestyle Intervention Are Influenced by the NYD-SP18 Variant - Suchánek, Pavel; Lánská, Věra; Hubáček, Jaroslav Alois (Central European journal of public health, 2015)
AIM: The study focuses on the analysis of the possible relationship between a common NYD-SP18 (rs6971091, G>A) gene polymorphism and weight loss after lifestyle intervention (combined dietary intake and physical activity) in overweight/obese females. METHODS: We genotyped 139 unrelated non-diabetic Czech females (49.5 ± 13.3 years, average BMI at baseline 32.2 ± 4.6 kg/m². Biochemical and anthropometrical measurements were performed before and after ten weeks of lifestyle intervention. CONCLUSION: Overweight/obese female carriers of the NYD-SP18 rs6971091 GG genotype exhibited a more beneficial response to the intensive lifestyle intervention than others.
Keywords: NYD-SP18; senioři; životní styl; Weight Loss; genotyp; jednonukleotidový polymorfismus; Obesity; cvičení; Genotype; Česká republika; polymorphism; Middle Aged; females; obesity; Life Style; Adult; Overweight; Czech Republic; redukční dieta; složení těla; proteiny aktivující GTPasu; ženské pohlaví; GTPase-Activating Proteins; Humans; hmotnostní úbytek; lidé středního věku; obezita; nadváha; Exercise; Body Composition; dospělí; intervention; Female; Aged; Diet, Reducing; lidé; Polymorphism, Single Nucleotide